Spiritual Development, Paradox, and Wisdom in Adult Educators’ Reflections Ageing - Elizabeth J. Tisdell (Adult Education Research Conference, 2010)
This paper discusses some of the longitudinal findings of a narrative study of spiritual development and emerging wisdom of women adult educators over a 10 year period.